Twenty-two years of the modular Consortium in the automotive industry - Pires, Silvio R. I.; Simon, Mateus L. [UNESP] (Taylor & Francis, 2020)
Using a longitudinal case study approach covering a period of twenty-two years, this article identifies the major changes and discusses why they occurred in the modus operandi of the only case of full Modular Consortium (MC) in the auto industry worldwide, established since November 1996 at the VW-MAN truck factory in Resende, Brazil. The key events and/or challenges, which occurred at the plant, were identified and discussed based on four main topics from the literature. Although the concept of modularity still continues to be used essentially in the production area, the current MC still maintains the basic principle of vehicle assembly being fully made by the seven module suppliers. Therefore, it remains a unique case in the auto industry and the maintenance of the essence of its modus operandi corroborates the satisfaction and positive evaluation of the MC by the companies that designed and operate it for over two decades.
Keywords: automotive industry; longitudinal study; modular Consortium; modularity; Supply chain management